1996
DOI: 10.1136/bmj.312.7023.83
|View full text |Cite
|
Sign up to set email alerts
|

Third generation oral contraceptives and risk of venous thromboembolic disorders: an international case-control study

Abstract: Risk of venous thromboembolism was slightly increased in users of third generation oral contraceptives compared with users of second generation products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
223
0
14

Year Published

1996
1996
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 559 publications
(241 citation statements)
references
References 10 publications
4
223
0
14
Order By: Relevance
“…During the 1990s, a variety of observational studies provided useful information regarding 'type A' ADRs (known as augmented reactions, which are dose dependent and predictable) of different drugs within a certain drug class (e.g., non-steroid anti-inflammatory drugs and gastrointestinal bleeding [8], selective serotonin reuptake inhibitors and upper gastrointestinal bleeding [9], third-generation oral contraceptives and venous thromboembolism [10][11][12]). During this period, other original articles passed unnoticed by the medical community and the RAs.…”
Section: Example 3: Nifedipine and Fatal Aplastic Anemiamentioning
confidence: 99%
“…During the 1990s, a variety of observational studies provided useful information regarding 'type A' ADRs (known as augmented reactions, which are dose dependent and predictable) of different drugs within a certain drug class (e.g., non-steroid anti-inflammatory drugs and gastrointestinal bleeding [8], selective serotonin reuptake inhibitors and upper gastrointestinal bleeding [9], third-generation oral contraceptives and venous thromboembolism [10][11][12]). During this period, other original articles passed unnoticed by the medical community and the RAs.…”
Section: Example 3: Nifedipine and Fatal Aplastic Anemiamentioning
confidence: 99%
“…In addition, we sampled serum lipids and the endothelium-derived substance endothelin-1, which is a potent vasoconstrictor and has recently become recognized for its association with vascular risk (21)(22)(23)(24). Owing to the fact that the vaginal ring uses a third-generation progestin, and recent evidence suggests that third-generation progestins may increase coagulation and thrombotic risk (25,26), we also measured baseline fibrinogen levels.…”
mentioning
confidence: 99%
“…In the third generation new progestin-formulas like desogestrel and gestoden were introduced (Speroff and DeCherney, 1993). Even though the latter preparations have less negative in¯uence on lipoproteins, new studies showed that the incidence of venous thromboembolism is even higher in women taking these new OC than in women using second generation OC (WHO, 1995;Jick et al, 1995;Spitzer et al, 1996). Therefore, other mechanisms for the impact of OC on cardiovascular disease require further investigation.…”
Section: Introductionmentioning
confidence: 99%